The Impact of Vitamin D Deficiency and its Outcome Among Patients With Ischemic Stroke (Medical Forum Monthly, 2024)
Objective: To determine the Impact of Vitamin D Deficiency and Its Outcome among Patients with Ischemic StrokeStudy Design: The cross-sectional descriptive studyPlace and Duration of Study: This study was conducted at the Liaquat University Hospital, Hyd from October, 2018 to March, 2019.Methods: The vitamin D status of each of the 370 patients who had ischemic stroke was investigated, and the results included readmission within 30 days, length of stay, and mortality.Results: The mean ± SD for age (yrs) 57.72±9.44, systolic blood pressure (mmHg) 160.94±7.82, diastolic blood pressure (mmHg) 115.72±11.74, duration of stroke (hrs) 41.95±8.86, random blood sugar (mg/dL) 290.77±18.95, fasting blood sugar (mg/dL) 150.84±9.96, hospital stay duration (days) 19.00±4.00 and vitamin D level (ng/ml) 12.76±6.51. Regarding vitamin D status, the percentages for sufficient, deficient and insufficient were 99 (26.7%), 200 (54%), 71 (19.1%), respectively. However, there was statistical significance in the vitamin D status with regard to gender (p=0.02), age (p<0.01), hospital stay (p<0.01), readmission (p<0.01) and mortality (p<0.01). Conclusion: Ischemic stroke has been independently linked with vitamin D deficiency.